Activity concentration of Fukushima-derived radiocesium in the western subarctic area of the North Pacific Ocean in summer 2017 - Kumamoto, Yuichiro; Aoyama, Michio; Hamajima, Yasunori; Murata, Akihiko (Journal of Radioanalytical and Nuclear Chemistry, 2020)
Abstract Vertical profiles of radiocesium ( 134 Cs and 137 Cs) were measured in the western subarctic area of the North Pacific in 2017. The highest concentration of 134 Cs, which was derived from the accident of the Fukushima Dai-ichi Nuclear Power Plant in 2011, was 0.14 Bq m −3 (or 1.19 Bq m −3 after the decay correction to the accident date). Although the vertical inventory of 134 Cs decreased between 2014 and 2017, the inventory in 2017 was larger than that expected. That was probably arose from the return of some portion of the high-concentration water mass along with the anticlockwise subarctic gyre current.